A Homocoupling Approach to the Key Dione of CyMe4-BTPhen – Vital Ligands for Nuclear Clean-Up by the SANEX Process - Trunks, Thomas M.; Babra, Jasraj Singh; Westwood, James; Smith, Christopher D. (SynOpen, 2022)
CyMe4-BTPhen and CyMe4-BTBP are the principal ligand systems used in Europe for the separation of actinides from lanthanides as a part of the SANEX process for nuclear recycling and reprocessing. We present a new approach to the synthesis of the CyMe4 fragment beginning from readily available hydroxypivalic acid. It features a cobalt-catalysed homocoupling of a neopentyl bromide to provide the key bisester precursor, thereby avoiding the requirement for technically challenging low-temperature LDA-mediated aldol chemistries.
Keywords: homocoupling; catalysis; nuclear clean-up; elemental separations; SANEX process; accident tolerant fuel